Actualization of Leadership as a Key Category of Neoeconomical Community: Socio-Cultural and Educational Aspects - Anna Gribovycz; Oksana Kondur; Yaroslav Melnyk (Vasyl Stefanyk Precarpathian National University, 2019)
The problem of leadership as a key category in the formation of a new generation of socially active and business people is examined in the article. To our time, the leadership and initiativeness are described in a large extent within the framework of the training of the university specialist category. It is proposed to bring it to a wide educational and professional position and to focus its attention on the university system. The reorganization of the higher educational system is also proposed, taking into consideration the need for actualization of leadership by itself. The results are interpreted in the framework of humanitarian, political, economic, social and demographic problems of Europe at the beginning of the XXI century.